Bandwidth Allocation Based on Traffic Load and Interference in IEEE 802.16 Mesh Networks - Sanjeev Jain; Vijay Shanker Tripathi; Sudarshan Tiwari (Journal of Engineering)
This paper introduces a traffic load and interference based bandwidth allocation (TLIBA) scheme for wireless mesh network (WMN) that improves the delay and throughput performance by proper utilization of assigned bandwidth. The bandwidth is allocated based jointly on traffic load and interference. Then a suitable path is selected based upon the least routing metric (RM) value. Simulation results are presented to demonstrate the effectiveness of the proposed approach which indicates higher bandwidth utilization and throughput as compared with existing fair end-to-end bandwidth allocation (FEBA).